Application of Fuzzy Logic in Neural Network Using Data Mining Techniques: A Survey - Sheela Jasmine, J (International Journal of Computer Sciences and Engineering, 2025)
The use of Neuro-Fuzzy Network is extremely wide in data mining due to some trademark like parallel performance, Self-organizing adaptive, power Also, shortcoming tolerance. Data mining models depend on errand they accomplish: Affiliation Rules, Clustering, Prediction, Also, Classification. Neuro-Fuzzy Network is utilized to find outline in data. The gathering of Neuro-Fuzzy Network model Also, data mining strategy can significantly increment the proficiency of data mining Techniques Also, it has been comprehensively used. Diverse Calculations have been discussed or streamlining the Manufactured Neuro-Fuzzy Network (ANN). ANN consolidates with other Calculations to find out the high exact data as compare to Conventional algorithm. The part of ANN utilizing data mining strategies is playing an imperative part in gauging or conjecture about diversions Also, weather. This produces high exact expectations than that of Conventional algorithm. Data mining approaches utilizing ANN can moreover work well. ANN is a highly class calculation which can be accelerated utilizing neuron. The result of which will produce a high speed up ANN. ANN can moreover be utilized or the reason of Evacuating rules from prepared Neuro-Fuzzy networks.